Impact of single nucleotide polymorphisms (R132Q and W120R) on the binding affinity and metabolic activity of CYP2C19 toward some therapeutically important substrates. (1st December 2020) - Derayea, Sayed M.; Tsujino, Hirofumi; Oyama, Yukiko; Ishikawa, Yoshinobu; Yamashita, Taku; Uno, Tadayuki
Abstract: Although CYP2C19 is minor human liver enzyme, it is responsible for the metabolism of many clinically important drugs. In this work, CYP2C19 wild type and its SNP mutants (R132Q and W120R) were prepared using over-expression system in E. coli, purified by column chromatography and their biological activities were compared. The enzyme activity toward certain drugs (amitriptyline, imipramine, lansoprazole and omeprazole) was investigated. Resonance Raman and UV–VIS spectroscopies revealed a minimal effect of SNP mutations on the heme structure. However, the mutation greatly affected the drug metabolism activities of CYP2C19. The degree of these effects was dependent on both the mutation and the chemical structure of the substrate. Surprisingly, the affected amino acid residue is located remotely from the heme center. Therefore, the direct effect of the mutation on the metabolic center is excluded. Alternatively, the significant impairment in the drug metabolism of these mutants could be attributed to a decrease in the electron flow to the iron center. Accordingly, understanding the effect of SNPs of CYP2C19, and the extents in which they participate in the drug metabolism, are important pillars that can enhance the therapeutic drugs efficacy and improve the patient outcomes toward the development of patient's tailored medicine.